The THE EPISTEMOLOGY OF THE QUR’ANIC INIMITABILITY (I‘JĀZ AL-QUR’ĀN) FROM ISSA J. BOULLATA'S PERSPECTIVE - Al Insyirah, Sofia Mawaddah (International Journal of Multidisciplinary Reseach, 2025)
The orientalists are sceptical about the originality of the Qur’an. Still, it turns out that Issa Joseph Boullata has another view by proposing the i’jāz (inimitability) as an indicator of the originality of the Qur’an. This study is important considering that the discourse of i’jāz Al-Qur’an has been studied theologically, which has made it more engaged by insiders. The purpose of this article is to explain how Boullata, as an outsider, also built his system in the i’jāz study. This research employs the library research method to gather data, which is then described and analysed using epistemological theory to provide an overview and focus for the research. Boullata formulated the idea of rhetorical arrangement (balāgy) in the Qur’an, which shows a very high literary taste. To find the rhetorical and aesthetic side of literature in the Qur’an, Boullata began i’jāz’s study by considering the Qur’an as a literary text, so that it would be separated from the theological realm. So, with this, Boullata confirmed the authenticity of the Qur’an based on the equality of the literature contained in it and made i’jāz an indicator of the originality of the Qur’an. This article focuses on the i’jāz aspect of the Qur’an from Boullata’s perspective. Further investigation regarding the impact of i’jāz on the originality of the Qur’an, according to Boullata, can be carried out to enrich the discourse on the study of the Qur’an and Orientalism.